The effect of antipsychotic medication and the associated hyperprolactinemia as a risk factor for periodontal diseases in schizophrenic patients: a cohort retrospective study - Rania Shalaby; Ahmed Elmahdy; Christine Mikhail (BMC, 2023)
Abstract Background Periodontal disease is a major health problem that results in tooth loss and thus affects oral health, which affects quality of life. In particular, schizophrenic patients are at higher risk for periodontal disease due to several factors, including the effect of antipsychotic medications received by those patients. Accordingly, the aim of the present cohort retrospective study is to explore the effect of antipsychotics on periodontal health and the possible effect of antipsychotic-induced hyperprolactinemia as a risk factor for periodontal disease progression in schizophrenic patients. Methods and outcomes The study population consisted of three groups: Group A (n = 21): schizophrenic patients that have been taking "prolactin-inducing" antipsychotics for at least 1 year; Group B (n = 21): schizophrenic patients who have been taking "prolactin-sparing" antipsychotics for at least 1 year; and Group C (n = 22): newly diagnosed schizophrenic patients and/or patients who did not receive any psychiatric treatment for at least 1 year. The study groups underwent assessment of periodontal conditions in terms of pocket depth (PD), clinical attachment loss (CAL), gingival recession, tooth mobility, and bleeding on probing (BOP). Also, bone mineral density was evaluated using DEXA scans, and the serum prolactin level was measured by automated immunoassay. Results Results revealed a statistically significant difference in PD, CAL, and serum prolactin levels (P ≤ 0.001, P = 0.001, and P ≤ 0.001, respectively) among the 3 study groups. For both PD and CAL measurements, group A has shown significantly higher values than both groups B and C, whereas there was no statistically significant difference between the values of groups C and B. Concerning serum prolactin levels, group A had significantly higher values than groups B and C (P ≤ 0.001 and P ≤ 0.001 respectively). There was a statistically significant difference (P ≤ 0.001) between the 3 study groups in terms of bone mineral density. Moreover, there was a statistically significant direct relation between serum prolactin level and other parameters including clinical attachment loss, pocket depth measurements and bone mineral density. Conclusion According to our results, it could be concluded that all antipsychotics contribute to the progression of periodontal disease, with a higher risk for prolactin-inducing antipsychotics. However, further long term, large sampled, interventional and controlled studies are required to reach definitive guidelines to allow clinicians properly manage this group of patients.